2014
DOI: 10.3390/e16094769
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mixed Working Fluids with Different Compositions in Organic Rankine Cycle (ORC) Systems for Vehicle Diesel Engines

Abstract: Abstract:One way to increase the thermal efficiency of vehicle diesel engines is to recover waste heat by using an organic Rankine cycle (ORC) system. Tests were conducted to study the running performances of diesel engines in the whole operating range. The law of variation of the exhaust energy rate under various engine operating conditions was also analyzed. A diesel engine-ORC combined system was designed, and relevant evaluation indexes proposed. The variation of the running performances of the combined sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Aghahosseini et al [22] conducted both energy and exergy analyses for ORCs with different pure and zeotropic working fluids. Yang et al [23] evaluated ORC recovery system performance with six types of mixture working fluids with different compositions. The case study showed that the The temperature of the engine exhaust gas is high; therefore, working fluids with high critical temperatures are selected to maintain the ORC within the subcritical range.…”
Section: System Design and Working Fluid Selectionmentioning
confidence: 99%
“…Aghahosseini et al [22] conducted both energy and exergy analyses for ORCs with different pure and zeotropic working fluids. Yang et al [23] evaluated ORC recovery system performance with six types of mixture working fluids with different compositions. The case study showed that the The temperature of the engine exhaust gas is high; therefore, working fluids with high critical temperatures are selected to maintain the ORC within the subcritical range.…”
Section: System Design and Working Fluid Selectionmentioning
confidence: 99%
“…Yang et al [56,57] analysed the use of zeotropic mixtures for WHR from the exhaust of a diesel engine. The heat source (i.e.…”
Section: Waste/exhaust Heat Recovery Orc Power Systemsmentioning
confidence: 99%
“…Several studies have been conducted in recent decades on the exploitation of the potential of binary mixture organic fluids as working fluid in organic Rankine cycles [7]. Some researchers aimed to utilize waste heat [8,9], while some investigated it for renewable sources, like solar and geothermal sources [10,11]. Compared to cycles utilizing high-grade heat sources, organic Rankine cycles (ORCs) often exhibit lower efficiency due to the utilization of low-grade heat [12].…”
Section: Introductionmentioning
confidence: 99%